2000
DOI: 10.1177/03635465000280060901
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Functional Knee Bracing on the Anterior Cruciate Ligament Strain Biomechanics in Weightbearing and Nonweightbearing Knees

Abstract: Functional knee braces are commonly prescribed after anterior cruciate ligament injury or reconstruction; however, their ability to protect the ligament, or graft, remains unclear. Our objective was to evaluate the anterior cruciate ligament strain response in braced and unbraced knees during weightbearing and nonweightbearing in combination with three externally applied loads: 1) anterior-posterior shear forces, 2) internal-external torques, and 3) varus-valgus moments. The Legend brace was tested. All extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 48 publications
1
33
1
2
Order By: Relevance
“…They can also reduce strain on the ACL for internal torques applied to the tibia up to 9 Nm in a non-weight-bearing condition when compared to an unbraced knee, but did not reduce strain values on the ACL when the knee was subjected to external torques (9 Nm) or varus-valgus moments (10 Nm) in weight-bearing and non-weight-bearing conditions (6,7). This protection can be put in perspective when compared to forces everyday activities exert on the ACL.…”
Section: Biomechanical Effects Of Bracingmentioning
confidence: 99%
“…They can also reduce strain on the ACL for internal torques applied to the tibia up to 9 Nm in a non-weight-bearing condition when compared to an unbraced knee, but did not reduce strain values on the ACL when the knee was subjected to external torques (9 Nm) or varus-valgus moments (10 Nm) in weight-bearing and non-weight-bearing conditions (6,7). This protection can be put in perspective when compared to forces everyday activities exert on the ACL.…”
Section: Biomechanical Effects Of Bracingmentioning
confidence: 99%
“…Our findings are consistent with those of previous researchers [15][16][17] who demonstrated a decrease in quadriceps muscle function and activation after aerobic exercise. Although numerous authors have looked at the effects of knee braces [18][19][20][21][22][23][24][25][26][27][28][29] and neoprene sleeves 10,30 on neuromuscular performance during dynamic activities, very few have compared these effects during a bout of aerobic exercise. Previous studies of knee bracing and neuromuscular function have indicated that knee braces 21,22,24,[26][27][28] decreased quadriceps muscle function and that neoprene sleeves 10,30 improved knee joint proprioception.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Human and surrogate models have been used to confirm the effects of bracing. Using arthroscopy, Beynnon et al, 7 implanted transducers into the ACL of patients to measure strain.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…This article focuses upon prophylactic braces, which are used to limit valgus stress injuries, and functional braces, which are used to prevent anterior translation of the tibia and to limit stress on anterior cruciate ligament-deficient and reconstructed knees. [5][6][7][8][9] The use, mechanism of action, clinical efficacy, and recommendation for prescription of prophylactic and functional braces are discussed as they apply to the prevention of ligamentous knee injuries in different patient populations. The Physician and Sportsmedicine Downloaded from informahealthcare.com by Fudan University on 05/16/15 For personal use only.…”
mentioning
confidence: 99%